2009
DOI: 10.1016/j.ijantimicag.2009.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Fosfomycin for the treatment of infections caused by multidrug-resistant non-fermenting Gram-negative bacilli: a systematic review of microbiological, animal and clinical studies

Abstract: The treatment of multidrug-resistant (MDR), extensively drug-resistant or pandrugresistant non-fermenting Gram-negative bacterial infections constitutes a challenge in an era of few new antibiotic choices. This mandates the re-evaluation of already existing antibiotics such as fosfomycin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
118
0
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(128 citation statements)
references
References 41 publications
5
118
0
5
Order By: Relevance
“…Fosfomycin was initially developed in Europe by CEPA and has been in use since the early 1970s, initially as an IV preparation of the disodium salt and later as an oral formulation of fosfomycin trometamol. Its primary use in Spain, Germany, France, Japan, Brazil, and South Africa has been as an oral treatment for urinary tract infections (UTIs) but it has also been used more broadly in other indications (Falagas et al 2008(Falagas et al , 2009(Falagas et al , 2010a. Fosfomycin was approved for use in the United States (as Monurol, fosfomycin tromethamine [same as trometamol]) in 1996 for treatment by singledose oral therapy of uncomplicated UTIs (acute cystitis) in women caused by Escherichia coli and Enterococcus faecalis.…”
mentioning
confidence: 99%
“…Fosfomycin was initially developed in Europe by CEPA and has been in use since the early 1970s, initially as an IV preparation of the disodium salt and later as an oral formulation of fosfomycin trometamol. Its primary use in Spain, Germany, France, Japan, Brazil, and South Africa has been as an oral treatment for urinary tract infections (UTIs) but it has also been used more broadly in other indications (Falagas et al 2008(Falagas et al , 2009(Falagas et al , 2010a. Fosfomycin was approved for use in the United States (as Monurol, fosfomycin tromethamine [same as trometamol]) in 1996 for treatment by singledose oral therapy of uncomplicated UTIs (acute cystitis) in women caused by Escherichia coli and Enterococcus faecalis.…”
mentioning
confidence: 99%
“…80 Others have found that various combinations of rifampin, ÎČ−lactams, aminoglycosides, quinolones, colistin/polymyxin B, fosfomycin or other agents are synergistic in vitro, or in animal models, against MDR Pseudomonas or Acinetobacter spp. 2,31,81,82 Many authors argue that rifampin should be considered for addition to other active antibiotics in the treatment of uncontrolled infection due to MDR bacteria, 31,55,78,83-85 though there is little evidence of why rifampicin should improve outcome and no randomized trials to show that it does improve these outcomes. Further obstacles include: (a) there is no relevant in vitro breakpoint for susceptibility to rifampin against Gram-negative bacteria; (b) toxic potential of rifampin; (c) multitude of drug interactions between rifampin and other agents, a main concern especially in onco-hematological patients and allogeneic HSCT recipients who receive a lot of other drugs concomitantly (such as cyclosporine, mycophenolate mofetil, antifungals, antivirals).…”
Section: Combination Therapy In Infections Due To Resistant Gram-negamentioning
confidence: 99%
“…1 Resistance also affects the choice of 'targeted' therapy once a pathogen has been isolated, identified and subjected to susceptibility testing. In some cases, treatment options are very limited, and the emergence and proliferation of multiresistant Gram-negative organisms -both Enterobacteriaceae and non-fermenters -is forcing the renewed use of old antibiotics, notably colistin/polymyxin B and fosfomycin [2][3][4][5][6] and of tigecycline. Similarly, the emergence of Gram-positive pathogens resistant to ÎČ-lactams and glycopeptides is leading to the use of linezolid, daptomycin and tigecycline in hematology patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Resistance to fosfomycin in P. aeruginosa results from the activity of the antibiotic-altering enzyme FosA (PA1129) (Bernat et al, 1997) or is caused by inactivation of the fosfomycin transport protein GlpT (PA5235) (Castañeda-GarcĂ­a et al, 2009). Due to its limited use and the relatively low level of reported resistance, fosfomycin has now been revisited for its possible effectiveness against MDR strains (Falagas et al, 2009).…”
Section: Introductionmentioning
confidence: 99%